The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.jctc.7b00059
|View full text |Cite
|
Sign up to set email alerts
|

Determining Atomistic SAXS Models of Tri-Ubiquitin Chains from Bayesian Analysis of Accelerated Molecular Dynamics Simulations

Abstract: Small-angle X-ray scattering (SAXS) has become an increasingly popular technique for characterizing the solution ensemble of flexible biomolecules. However, data resulting from SAXS is typically low-dimensional and is therefore difficult to interpret without additional structural knowledge. In theory, molecular dynamics (MD) trajectories can provide this information, but conventional simulations rarely sample the complete ensemble. Here, we demonstrate that accelerated MD simulations can be used to produce hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…As mentioned in the introduction, there are several ways to combine MD simulations with SAS data (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), but we here used the Bayesian/Maximum Entropy (BME) method (3) and the above-calculated SAXS and SANS intensities to reweight the trajectories. For details of BME see (3) as well as code and examples online https://github.com/KULL-Centre/BME.…”
Section: Combining MD Simulations and Sas Data By Bayesian Reweightingmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, there are several ways to combine MD simulations with SAS data (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), but we here used the Bayesian/Maximum Entropy (BME) method (3) and the above-calculated SAXS and SANS intensities to reweight the trajectories. For details of BME see (3) as well as code and examples online https://github.com/KULL-Centre/BME.…”
Section: Combining MD Simulations and Sas Data By Bayesian Reweightingmentioning
confidence: 99%
“…In that case, however, simulations and experiments may be used synergistically to generate and refine the description of flexible molecules. Thus, as described by us and others, SAXS and molecular simulations can be combined to determine a structural ensemble that represents the system, and is compatible with the information in the force field and the experimental constraints from SAXS (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 96%
“…Simulations have been used to predict chemical shifts and directly compare these results to nuclear magnetic resonance (NMR) experiments [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Simulations have also been used to recapitulate small angle X-ray scattering (SAXS) data [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Temporal information can be gleaned in NMR or SAXS by a diverse variety of means, including peak broadening in NMR, or by performing SAXS in timeresolved modes [38].…”
Section: Introductionmentioning
confidence: 99%
“…The BEES algorithm is designed to find the theoretical solution ensemble that uses the fewest number of populations to accurately describes the experimental data. This algorithm is briefly presented here ( Fig 1), but further details can be found in the supplemental text and elsewhere 22 . In short, experimental data are gathered and post-processed prior to using the BEES module.…”
Section: Bees Algorithmmentioning
confidence: 99%
“…This approach, which is an extension of the BSS-SAXS technique 13 , compares solution ensembles of a variety of sub-ensembles from a combination of potential scattering states. Originally, we used this method to fit ensembles of covalently linked ubiquitin trimers, and we observed that the algorithm could produce ensemble models that robustly resisted overfitting 22 .…”
Section: Introductionmentioning
confidence: 99%